(untitled) (Al-Academy, 2022)
The products of the surrealist school since its inception to this day have greatly influenced art in the world, so we find many artists around the world invested in their visual texts the forms generated by surrealism, and here the researcher raises several questions: What are the formal vocabulary that directly or indirectly refers to Self-used by the surrealist painter? Was the surrealist form understood as intended by the movement? In these questions, the research problem is summarized. The importance of it lies in identifying the references to the form of the human self, which are related to the psychological field in the works of the surrealists, especially Salvador Dali. Then the researcher chose his research community from the works that were completed in the period 1927-1964 and chose three samples and after the analysis, the researcher reached the results and conclusions, including:1. The three models of Dali (1), (2), (3) included critical analysis based on hallucinations.2. The intention of mental confusion through the naming in the sample (1).3. The use of dream symbols from the book (The Interpretation of Dreams) by the psychologist (Freud) and its formation of dream topics, but in a well-studied scientific way and not from the artist’s subconscious and dreams